2015
DOI: 10.1002/cctc.201500151
|View full text |Cite
|
Sign up to set email alerts
|

Effect of VOx Species and Support on Coke Formation and Catalyst Stability in Nonoxidative Propane Dehydrogenation

Abstract: VOx/SiO2–Al2O3 catalysts were prepared by grafting vanadyl acetylacetonate onto the supports with a SiO2 content between 0 and 100 wt. %. The degree of polymerization of VOx species and acidity both of pristine supports and the catalysts were evaluated. To determine their on‐stream stability and carbon deposition activity in nonoxidative propane dehydrogenation, continuous‐flow tests and in situ thermogravimetric measurements were performed. The rate constants of catalyst deactivation and carbon deposition wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
50
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 54 publications
7
50
0
Order By: Relevance
“…However, most catalysts were prepared by impregnating vanadium‐containing solution on an available alumina and subsequent calcination process. The introduced VO x species usually decrease the specific surface area of the resulted catalysts ,. This phenomenon can be observed not only on alumina, but also on other supports, like SiO 2 –Al 2 O 3 , MCM‐41, MSU‐1 .…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, most catalysts were prepared by impregnating vanadium‐containing solution on an available alumina and subsequent calcination process. The introduced VO x species usually decrease the specific surface area of the resulted catalysts ,. This phenomenon can be observed not only on alumina, but also on other supports, like SiO 2 –Al 2 O 3 , MCM‐41, MSU‐1 .…”
Section: Introductionmentioning
confidence: 94%
“…Alumina, as a frequently used support with stable structure and high specific surface area, has been widely used to prepare catalysts ,,. Vanadium oxide catalysts with porous alumina as support have been widely studied in the dehydrogenation of C 3 –C 4 alkanes ,,. However, most catalysts were prepared by impregnating vanadium‐containing solution on an available alumina and subsequent calcination process.…”
Section: Introductionmentioning
confidence: 99%
“…As expected, with increasing metal loading, the edge energy decreased from 3.9 eV to 2.5 eV, indicating the increase in polymerization degree and the growth in domain size of vanadium oxides. [29][30][31] Previous studies have suggested that monovanadates, polyvanadate and V 2 O 5 formed at different vanadium densities:…”
Section: Structure Analysis Of Vo X /Al 2 O 3 Catalystsmentioning
confidence: 99%
“…4,29 In Figure 6a, carbonaceous material was 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 14 observed covering the 12V/Al catalyst after 4 h-PDH reaction, and the amount of coke deposition (i.e., 0.054 g/g cat ) was measure by TGA (Figure 6b). …”
Section: Catalytic Performancementioning
confidence: 99%
“…Many other promising catalytic systems that are less hazardous for the environment than chromium or cheaper than platinum are being investigated, and are based on vanadium [10,11,12], gallium [13,14], iron [15,16], tungsten [17] or indium [18] oxides. In most cases, catalytically active compounds are deposited on supports characterized by a large specific surface area and accessible pore system.…”
Section: Introductionmentioning
confidence: 99%